Facile acid treatment of multiwalled carbon nanotube-titania nanotube thin film nanocomposite membrane for reverse osmosis desalination. (20th April 2018) - Wan Azelee, I.; Goh, P.S.; Lau, W.J.; Ismail, A.F.
Abstract: Thin film composite (TFC) reverse osmosis (RO) membrane, which has been widely applied for desalination, consists of an ultra-thin polyamide (PA) coating layer that supported on a porous support membrane. The main interest of this work is to perform facile acid modification on the polysulfone (PS) support of TFC and thin film nanocomposite (TFN) membranes. The PS support was acid treated with sulfuric acid (H2 SO4 ) at a concentration ranging from 1 to 2 M for 24–72 h. Response surface methodology (RSM) based on historical data design (HDD) was used to verify the optimum condition of support membrane with respect to NaCl rejection and water permeability. The highest water permeability was achieved at 1.13 L/m 2 .h.bar when nanoparticles loading of 0.03% was incorporated into the PA layer and PS support treated at 1.5 M H2 SO4 for 48 h. The NaCl rejection of all the synthesized membranes was found to be above 96%. Graphical abstract: Proposed elongation effect on the PS support surface, (a) during acid treatment, (b) during washing, and (c) after washing. Image 1 Highlights: Facile acid treatment was conducted on the polysulfone (PS) support membrane. Response surface methodology (RSM) was used to verify the optimization. Modified support membrane improved water permeability of TFN embedded a-MWCNT-TNT.